Recent social trends in West Germany 1960-1990 - Glatzer, Wolfgang (Comparative charting of social change, 1992)
This volume examines social trends in West Germany during the period between 1960 and 1990. This was a special phase of German history: the Federal Republic of Germany was founded in 1949, and by 1960 the main disturbances of the Second World War had been overcome. The next thirty years saw relatively stable development in democratic institutions, economic wealth, and the welfare state. This process, however, was not entirely without difficulties. Environmental conditions deteriorated and unemployment grew, especially in the 1980s. A new, reunified Germany replaced the "old" FRG in 1990, ushering in a fundamentally different social structure.